Serious Games as tools for food and nutrition education: a systematic review - Ponte, Iago Almeida da; Silva, Bruno Bezerra da; Batista, Lia Loiola Maia (ABCS Health Sciences, 2024)
Serious games emerge as teaching tools with a purpose beyond entertainment, aiming to improve some aspect of the teaching-learning process. Given the high prevalence of chronic noncommunicable diseases in the Brazilian population, this study aimed to evaluate, through a systematic literature review, the potential of serious games as a tool for Food and Nutrition Education. To this end, we searched the PubMed, Biblioteca Virtual de Saúde, and SciELO databases for articles published in the last five years in english and portuguese. A total of 63 studies were identified, of which only 10 met the inclusion and exclusion criteria established for this review. Most studies reported positive outcomes with the use of serious games as an educational tool, finding positive effects on the retention of knowledge learned about food and nutrition, and their use showed promise as an alternative to traditional teaching methodologies. Despite this, the studies had limitations regarding the duration of the interventions and the representativeness of their sample sizes, indicating the need for future studies with methodological designs that fill such gaps. This review shows that gamified approaches to nutrition education seem promising in the context of the teaching-learning process but still lack methodological standardization for interventions based on serious games to be validated as a tool for Food and Nutrition Education.